KOMPARASI KARAKTERISTIK KEUANGAN PERUSAHAAN INTERNASIONAL DAN PERUSAHAAN DOMESTIK PADA SEKTOR MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2009-2014 - Rendy Sentosa; Deddy Marciano; Endang Ernawati (Perpustakaan Universitas Surabaya, 2017)
ABSTRACT - This research has two purposes. The first purposes is to examine the differences between multinational companies and domestic companies. The second purposes is to examine the impact of internationalization, profitability, agency cost of debt, firm’s size, business risk and foreign exchange risk to the company’s capital structure, which is measured by leverage. This research’s objects is manufacturing companies which is listed in Indonesia Stock Exchange in 2009-2014. Univariate test is used to examine the differences between multinational companies dan domestic companies. Univariate test shows that multinational companies have higher leverage, lower profitability, higher agency cost of debt, higher business risk and higher foreign exchange risk than domestic companies. Multiple linear regression is used to examine the impact of independent variables to dependent variable. The equation in this research use linear and quadratic equation. The result is internationalization, firm’s size and business risk has positive impact to leverage, while profitability, agency cost of debt and foreign exchange risk has negative impact to leverage. The result of quadratic model shows that internationalization has negative impact only in the first stage of internationalization, then on the next stage, internationalization has positive impact to leverage. Keywords: Capital Structure, Internationalization,Univariate Test, Multiple Linear Regression.